Effects of dietary supplementation of peppermint (Mentha piperita) on growth, survival and haemato-biochemical profile of common carp (Cyprinus carpio) fingerlings - Basant Singh; Yogendra Nishad; B. Nightingale Devi; Dushyant Kumar Damle; Kamalesh Panda; Jham Lal; Soibam Ngasotter; . Tameshwar (Journal of Fisheries, 2026)
Herbal feed additives are increasingly explored in aquaculture as natural alternatives to synthetic growth promoters and immunostimulants. Peppermint (Mentha piperita), known for its bioactive phytochemicals and antioxidant properties, has shown potential benefits for fish health and metabolism. A 60-day feeding trial was conducted using 120 fingerlings (initial mean weight: 10.2±0.02 g; length: 9.63±0.03 cm) randomly distributed into four experimental groups, each with three replicates, following a completely randomized design. Experimental diets were prepared by incorporating peppermint leaf powder at 0% (control), 1%, 2%, and 3% per kg of feed weight (designated as T1, T2, and T3, respectively). After 60 days, fish fed the diet containing 3% peppermint (T3) exhibited significantly higher (p < 0.05) weight gain, protein efficiency ratio, average daily growth, and specific growth rate compared to other treatments. A significant increase (p < 0.05) in white blood cell (WBC) count was also recorded in the T3 group, indicating enhanced immune response. No significant differences were observed in red blood cell count, haemoglobin, packed cell volume, platelets, lymphocytes, monocytes, mean corpuscular hemoglobin concentration, mean corpuscular hemoglobin, or mean corpuscular volume among treatments. No mortality was observed in any group throughout the experimental period. Overall, dietary supplementation with 3% peppermint leaf powder improved growth performance, stimulated immune function, and maintained normal hematobiochemical parameters in common carp, supporting its potential as a safe and effective natural additive in sustainable aquaculture.